(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
Maize is one of the most important cereal crops worldwide, yet its productivity is severely reduced by abiotic and biotic stresses. Optimization of cultivation technologies through the use of biological and biodynamic preparations in combination with growth stimulants is considered a promising approach to enhancing crop resilience. The aim of this study was to evaluate the effectiveness of integrated anti-stress technologies in improving maize performance. The field experiment included three variants of foliar treatments with biological preparations based on Trichoderma spp. and Pseudomonas spp., multifunctional growth stimulants, and biodynamic agents. Physiological and biochemical plant parameters, ear morphology, and grain yield were assessed. The results showed that the application of biological preparations combined with growth stimulants increased ear length by 1.0 cm, ear weight by 38–46 g, grain number per ear by 47–49, and thousand kernel weight by 13–20 g compared to the control. Grain yield increased by 12.9–14.9 %, with the strongest effect observed under combined use of biological, growth-stimulating, and biodynamic agents. The practical significance of the study lies in demonstrating the feasibility of implementing integrated anti-stress systems into maize cultivation technology, which enhances crop productivity and yield stability under climate change conditions.